To see or not to see? That is one of the questions - Castellano San Jacinto, Tania (Re-visiones, 2024)
With his behaviour, Object – the main character in Samuel Beckett’s Film (1965) – aims to escape from everybody else’s gaze, and even from his own, according to George Berkeley’s core idea "to be is to be perceived". This guiding thread will show us how perceptive substraction implies as much of an escape as an alternative: by substracting visual material, the subject endeavours to stay on the sidelines and to distance himself from what he perceives. With this, he tries to reach a degree zero where he will no lonfer be able to see and/or be seen, and from which he will be able to see and/or be anew. This radical rupture with what is given to perceive is repeated in art trends such as the Structural Film. Its vertiginous flicker of monochromes aims to refresh an exhausted gaze absorbed by the media. This is the way the Benaminian destructive character, known by "the need for fresh air and open space", operates as much in film structuralists as in Object. It is a way to take a breath and start anew.